An Assessment of the Effects of Navigation Maps on Drivers' Mental Workloads. Issue 3 (June 2014) - Chao, Chin-Jung; Lin, Chia-Hsyang; Hsu, Shang-Hwa
This study compares the mental workloads and subjective feelings of drivers navigating different road patterns using different formats of electronic and paper maps. The results show drivers experience lower mental workloads when using 2D electronic maps compared to 3D electronic maps. Significant differences in galvanic skin responses were observed for navigation map formats with different road intersection patterns. The low- and high-frequency components of heart rate variability showed significant differences between map formats for regular road intersections, but no significant differences between map formats for irregular road intersections. Statistically significant effects on subjective feelings were found between different map formats and road intersection patterns. The wider implications of the study results for the design and use of navigation map interfaces are discussed.